Using theory of reasoned action to explain taxpayer intention to comply with goods and services tax - Bidin, Zainol; Mohd Shamsudin, Faridahwati; Othman, Zainudin (Centre for Promoting Ideas, 2014)
The aim of this study is to investigate the perception of taxpayers towards the implementation of good and services tax (GST) in Malaysia.Theory of reasoned action proposed by Fishbein and Ajzen (1975) was used as the underlying theory for the study. One hundred and three respondents in Kedah and Perlis participated in the study.Multiple regressions were employed to examine the relationship between attitude and subjective norms on behavioural intention to comply with GST. Results showedthat attitude and subjective norms variables were significantly and positively related to behavioural intention.All these independent variables were able to explain 28% of the variance in behavioural intention to comply with GST. Implications and recommendations for policy makers are discussed.